Eko-Sufisme Islam Aboge Masjid Saka Tunggal Cikakak Banyumas - Mochammad Lathif Amin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This research aims to explore environmental ethics based on spirituality (eco-sufism) by exploring the cultural values of Islam Aboge Cikakak in the effort to address the environmental crisis. This research uses a qualitative approach. Data were collected through observation methods, interviews, and documentation in relation to: 1) the teaching, 2) tradition, 3) cultural values, and 4) environmental consciousness. The collected data were then analyzed using constant comparison. The research found that the root of Islam Aboge’s culture is the acculturation between Islam and the Kejawen tradition, which was taught by Kiai Mustholih. This includes the Aboge (Alip Rebo Wage) Calendar, the Jaro Jab tradition, Muludan, and the Saka Tunggal Mosque (the oldest mosque in Indonesia). The eco-sufism of Islam Aboge is concluded in the life interpretation of being ‘for God’ and having to ‘return to God’. The symbolic meaning of the name of the year in the Aboge Calendar (ana-ana tumandang gawe lelakon urip bola bali marang suwung) reflects a full and total comprehension of the unity of being (God–man–nature), the transformation of self: natas, nitis, and netes.